The Mapping of Argument on the Indonesian Capital City (IKN) Relocation Policy - Nugroho, Rino Ardhian; Kumar, Ahlul Wursita; Sudarmo, Sudarmo; Prakoso, Septyanto Galan (Jurnal Review Politik, 2024)
This research examines the Argument Mapping Method for structuring the Indonesian Capital City Relocation Policy problem. The arguments were obtained from online media, online petitions and social media. The collected data was processed by crawling data using Netlytics software and than visualize it by Gephi. By using Argument Mapping, this research seek to find out which actors and its arguments and then grouping the arguments into pros and cons. This research shows that there are differences influence of actors and meta problems that cause pros and cons on social media regarding the development of the National Capital, namely Institutional or Governance problem